Maintenance therapies for Hodgkin and non-Hodgkin lymphomas after autologous transplantation: a consensus project of ASBMT, CIBMTR, and the Lymphoma Working Party of EBMT - Kanate, Abraham S.; Dreger, Peter (JAMA oncology, 2019)
Importance: Maintenance therapies are often considered as a therapeutic strategy in patients with lymphoma following autologous hematopoietic cell transplantation (auto-HCT) to mitigate the risk of disease relapse. With an evolving therapeutic landscape, where novel drugs are moving earlier in therapy lines, evidence relevant to contemporary practice is increasingly limited. The American Society for Blood and Marrow Transplantation (ASBMT), Center for International Blood and Marrow Transplant Research (CIBMTR), and European Society for Blood and Marrow Transplantation (EBMT) jointly convened an expert panel with diverse expertise and geographical representation to formulate consensus recommendations regarding the use of maintenance and/or consolidation therapies after auto-HCT in patients with lymphoma. Observations: The RAND-modified Delphi method was used to generate consensus statements where at least 75% vote in favor of a recommendation was considered as consensus. The process included 3 online surveys moderated by an independent methodological expert to ensure anonymity and an in-person meeting. The panel recommended restricting the histologic categories covered in this project to Hodgkin lymphoma (HL), mantle cell lymphoma (MCL), diffuse large B-cell lymphoma (DLBCL), and follicular lymphoma. On completion of the voting process, the panel generated 22 consensus statements regarding post auto-HCT maintenance and/or consolidation therapies. The grade A recommendations included endorsement of: (1) brentuximab vedotin (BV) maintenance and/or consolidation in BV-naïve high-risk HL, (2) rituximab maintenance in MCL undergoing auto-HCT after first-line therapy, (3) rituximab maintenance in rituximab-naïve FL, and (4) No post auto-HCT maintenance was recommended in DLBCL. The panel also developed consensus statements for important real-world clinical scenarios, where randomized data are lacking to guide clinical practice. Conclusions and Relevance: In the absence of contemporary evidence-based data, the panel found RAND-modified Delphi methodology effective in providing a rigorous framework for developing consensus recommendations for post auto-HCT maintenance and/or consolidation therapies in lymphoma.
Gesehen am 30.09.2019